Emerging Realities in the International Political System: Transforming State’s Foreign Policy - Zaidi, Syed Muhammad Saad (Herald of the Russian Academy of Sciences, 2023)
Geopolitical evolution is a constant process; thus, the international system has transformed time and again. However, with rapid technological advancement, the transformation cycle of the international system has substantially been reduced. Hence, in less than two decades since the unipolar moment commenced, there begun chatter of a political paradigm shift. The root cause being the decline of the United States and rise of major powers; China, Russia, and India. Whereas, multiple intervening factors, newly emerged realities, such as emergence of non-state actors, rise of the East, the increasing scale of regionalization, the shift towards neo-nationalist foreign policy, the advent of fifth-generation technological warfare, and rising ecological issues, identified as catalyst to the paradigm shift. Nonetheless, these newly emerged realities have also a profound effect on the foreign policy orientation of states. This paper objectively and critically analyzes how the emerging realities in the international system are affecting the foreign policy of states.